Imaging spectrum of breast papillary lesions: With special emphasis on atypical appearances - Toprak, Hüseyin; Yıldız, Şeyma; Aralaşmak, Ayşe; Aydın, Sinem; Bilgin, Sabriye Şennur (Bentham Science Publ Ltd, 2016)
Papillary breast tumors are rare breast tumors. Presentation of papillary breast lesions varies clinically and radiologically. Standard diagnostic work-up for papillary breast lesions includes various radiological modalities such as mammography, galactography, ultrasound and MRI. Papillary lesions often have a wide spectrum of appearance on different radiological modalities, so that optimal differentiation of papillary lesions is not easy with various imaging methods. The purpose of this review article is to describe the different imaging appearances of benign and malignant papillary lesions of the breast with special emphasis on atypical appearances.
WOS: 000387420100002
Keywords: Breast; Magnetic Resonance Imaging; Mammography; Papillary Lesions; Ultrasound